Gutter Ordering Application Design Using The SDLC Method On CV Android - Rini Amalia; Sri Melati Sagita; Achmad Faisal (Journal of Information System, Informatics and Computing, 2022)
Technological developments can help in designing a CV. Reka Baja Utama, where the ordering system is designed to support the functioning of the current ordering system. The methodology used is System Development Life Cycle (SDLC) with roles in several stages of web information system development such as system planning, systems analysis, system design/design, system implementation/implementation and system maintenance. In the process of ordering and selling a lot of guttering products the drawback, namely the difficulty in ordering guttering products that still use the manual system. Android-based applications can make it easier for CV customers. Main Steel Design in conducting Gutter Ordering transaction